A Drug Stability Study Using Surface-Enhanced Raman Scattering on Silver Nanoparticles - Hulya Yilmaz; Mustafa Culha (Applied Sciences, 2022)
Pharmaceutical product quality is of vital importance for patient safety. Impurities and potential degradation products can cause changes in chemistry, pharmacological and toxicological properties by having a significant impact on product quality and safety. Stress-testing (forced degradation) studies of pharmaceutical preparations became necessary to assure degradation mechanisms and potential degradation products. Consequently, it is crucial to understand the nature of possible degradation products. Surface-enhanced Raman spectroscopy (SERS) is a powerful vibrational spectroscopic technique that can provide valuable information about changes in a molecular structure with its intrinsic finger-print property. In this study, a forced degradation study was conducted on pemetrexed (PMT), an antifolate chemotherapy drug, in order to identify its likely chemical degradation products. The degradation mechanism of PMT was investigated under various experimental conditions; basic (0.1 M NaOH), acidic (0.1 M HCl), and oxidative (3% H2O2v/v). We used silver nanoparticles (AgNPs) of average size 60 nm as SERS substrates. The study shows that SERS can be a fast and reliable technique to study the stability and possible degradation mechanisms of drugs under several different conditions.